Hydrothermal decomposition of pentachlorophenol in subcritical and supercritical water with sodium hydroxide addition - Prabowo, Benedictus; Veriansyah, Bambang; Kim, Jae-Duck (SCIENCE PRESS, 2007)
Hydrothermal decomposition of pentachlorophenol (PCP, C6HCl5O), as the probable human carcinogen, was investigated in a tubular reactor under subcritical and supercritical water with sodium hydroxide (NaOH) addition. The experiments were conducted at a temperature range of 300-420 degrees C and a fixed pressure of 25 Wa, with a residence time that ranged from 10 s to 70 s. Under the reaction conditions, the initial PCP concentrations were varied from 0.25 to 1.39 mmol/L and the NaOH concentrations were varied from 2.5 to 25 times of the concentrations of PCP. The result of this study showed that PCP conversion in supercritical water was highly dependent on the reaction temperature, residence time, and NaOH concentration. PCP conversion in subcritical water is, however, only dependent on reaction temperature. NaOH concentration and residence times were found to have little effect on PCP conversion in subcritical condition. It was found that NaOH concentration affected the dechlorinations of PCP in the supercritical water. The intermediates detected were proposed to be tetrachlorophenol and trichlorophenol, respectively.
Keywords: OXIDATION; THIODIGLYCOL; KINETICS